2021
DOI: 10.1002/nau.24820
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of 100U of Onabotulinum toxin A on detrusor contractility in women with idiopathic OAB: A multicentre prospective study

Abstract: Aims: Intradetrusor injection of Onabotulinum Toxin A (BTX-A) is a thirdline treatment for overactive bladder (OAB). Voiding dysfunction and the need for intermittent catheterization are potential complications, consequent to bladder contractility (BC) decrement. Primary aim: to evaluate BC variation after BTX-A detrusor injection in women with idiopathic OAB. Methods: A prospective multi-institutional observational study was conducted.Medical history, bladder diary, 24-h pad test, and invasive urodynamic para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…8 PIP1 did not show any statistically significant variation after botulinum toxin injection (42 cmH2O ranging from 38.3 to 48 before treatment; 42 cmH2O ranging from 35 to 47.1 after treatment), which led us to conclude that 100 U of BTX-A cannot influence bladder contractility while maintaining the therapeutic effects on symptom relief and bladder storage function. 1 We agree that PIP1 has some limitations too. One of them is ignoring the contribution of abdominal pushing during micturition.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…8 PIP1 did not show any statistically significant variation after botulinum toxin injection (42 cmH2O ranging from 38.3 to 48 before treatment; 42 cmH2O ranging from 35 to 47.1 after treatment), which led us to conclude that 100 U of BTX-A cannot influence bladder contractility while maintaining the therapeutic effects on symptom relief and bladder storage function. 1 We agree that PIP1 has some limitations too. One of them is ignoring the contribution of abdominal pushing during micturition.…”
mentioning
confidence: 83%
“…The median PIP1 of the cohort of patients enrolled was 42 cmH2O (interquartile range: 38.3-48 cmH2O), instead of 29 cmH2O. 1 This feature is fundamental, as we treated women with normocontractile detrusors. PIP1 lower than 50 cmH2O would mean administrating BTX-A to bladders with reduced contractility.…”
mentioning
confidence: 99%
“…In women with OAB, a significant reduction in the DO rate and an increase in the median maximum cystometric capacity were noted after Botox injection for idiopathic DO. The maximum flow rate (Qmax), detrusor pressure (Pdet), and PVR all showed no significant change, and no patient required catheterization after Botox injection [ 19 ].…”
Section: Clinical Application Of Botox On Oab: Efficacy Adherence Adv...mentioning
confidence: 99%
“…Current application of botulinum toxin A on lower-urinary-tract diseases or dysfunctions. ,[7][8][9][10][11][12]15,16,18,19,33,[35][36][37][38] …”
mentioning
confidence: 99%
“…The article "Evaluation of the effect of 100 U of Onabotulinum toxin A on detrusor contractility in women with idiopathic OAB: A multicentre prospective study" by De Rienzo et al 1 showed in a very good way that females older than 18 years (with a mean age of 54.6 years), with projected isovolumetric pressure 1 (PIP1) ≥29 cmH 2 O and postvoid residual volume less than 100 ml, with overactive bladder that did not respond to first-line treatments, responded well to intradetrusor injection of 100U of Onabotulinum toxin A (BTX-A), without causing voiding dysfunction. Although this conclusion is correct, we would like to make a theoretical analysis of why we think that it is probably not possible to say that "contractility was the only parameter that resulted unchanged after BTX-A injection".…”
Section: Dear Editormentioning
confidence: 99%